Agricultura familiar e pecuária leiteira : um estudo dos assentamentos nos municípios de Peabirú e Quinta do Sol - Souza, João Batista da Luz de (2010)
This paper aims to conduct a survey describing the production and marketing of milk in the region of settlements in the municipalities of Peabirú and Quinta do Sol in the state of Paraná. After that, to examine if there are conditions to dairy farmers achieving a higher economic development level in the activity. We used the methodological approach of the case study, the main sources of evidence interviews conducted in eighty-nine producers and the two dairy serving the area. Also were used documentation, files, observations and participatory observations. The results point to a possible exclusion of producers in order to lower production specialization which is one of the determining factors for the development of family farming in milk production. Institutional change that has suffered the dairy agribusiness system had different implications for competitive dynamics of the market and this has been reflected in the incentives provided to producers. Soon, the situation in the region is not sustainable, nor for the producers and not for the dairy industry who perform the capture of milk.